THE EXISTENCE OF ALFAMART AND INDOMARET: THE IMPACT ON THE SUSTAINABILITY OF SMALL TRADERS IN THE INDONESIA-MALAYSIA BORDER REGION - Sri Deti; Abdul Rizal (Cross-Border Journal of Business Management, 2021)
The presence of Indomaret in Galing Village, Galing District in 2016 and followed by Alfamart in 2018 raised public concerns, especially small traders, that the presence of the two modern stores would threaten the business continuity of small traders. This study uses a descriptive qualitative approach, with the data sources used are small traders in Galing Village whose store locations are adjacent to Alfamart and Indomaret. Data collection techniques using observation, interviews, and documentation. The results showed that from four aspects such as capital, human resources, production and marketing carried out by small traders in Galing Village, they were far below the capabilities possessed by Alfamart and Indomaret, however, although affected by the presence of Alfamart and Indomaret, the businesses run by the small traders do not necessarily close. These businesses can still run because they already have their customers. Not everyone in rural areas likes to shop at minimarkets and not all the things people need are in modern stores. Then in terms of business competition between small traders in Galing Village with Alfamart and Indomaret, it is following a business competition in Islam, namely from the side of the competing parties, the way of competing and the object being competed does not violate Islamic law.